Defining the pathophysiological impact of cigarette smoke extract in mice as a model for Chronic Obstructive Pulmonary Disease (COPD) - Bartlett, Laura Grace (2024)
INTRODUCTION: Chronic obstructive pulmonary disease (COPD) is a progressive, long-term group of respiratory diseases that encompasses chronic bronchitis and emphysema, and is typically caused by chronic cigarette smoke (CS) exposure. Although it is currently listed as the third leading cause of mortality worldwide by the WHO, current understanding of COPD pathophysiology is limited and as such the disease is frequently underdiagnosed or misdiagnosed. One of the hallmark characteristics of COPD is chronic and persistent inflammation, and much of our current understanding of the immunopathogenic mechanisms of COPD comes from the use of whole-body or nose-or-head only CS-exposure mouse models. Despite the existence of such models, these are not permitted for use under UK laws protecting the use of animals in science, as the model systems are considered to place mice under significant unnecessary stress and harm, and phenotypic outcomes do not accurately mimic human disease. Therefore, this project aims to develop a novel CS-exposure murine model of COPD that encompasses the three Rs of animal research (replacement, refinement and reduction) to improve model design in regards to both animal welfare and applicability to human disease.